2004
DOI: 10.1097/00005537-200409000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Edaravone on Streptomycin‐Induced Vestibulotoxicity in the Guinea Pig

Abstract: The study results suggest that topical administration of edaravone better suppresses streptomycin-induced vestibulotoxicity than systemic administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…These findings are quite similar to those observed when using L-NAME [10] or when using the aminoglycoside ototoxicity model [21,22]. Furthermore, we compared systemic and topical administration groups regarding the protective effects of edaravone.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are quite similar to those observed when using L-NAME [10] or when using the aminoglycoside ototoxicity model [21,22]. Furthermore, we compared systemic and topical administration groups regarding the protective effects of edaravone.…”
Section: Discussionsupporting
confidence: 83%
“…The results indicated that topical administration suppressed PaExoA-induced auditory disorders better than systemic administration. A similar result was also observed regarding streptomycin-induced vestibulotoxicity [22]. Why topical administration should have been superior to systemic administration was not evident, but the high concentration of edaravone in the inner ear may have been responsible.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Aminoglycosides are capable of stimulating the formation of reactive oxygen species that play an important role in inner ear damage. This damage is ameliorated by the presence of free radical scavengers [11] . The presence of nitric oxide synthase was demonstrated in the vestibular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Edaravone is a free radical scavenger capable of trapping several free radicals. In the inner ear, edaravone has demonstrated a protective effect on noise-induced cochleopathy in the guinea pig [9], in streptomycin-induced vestibulotoxicity in the guinea pig [18], and in Pseudomonas aeruginosa-inflicted cochleopathy in rat [8].…”
Section: Discussionmentioning
confidence: 99%